Data-Based Program Design Using Implementation Science Frameworks. - Smith-Miller, Cheryl A. (Research & Theory for Nursing Practice, 2025)
Background: Integrating evidence into nursing practice remains challenging due to gaps in nurses' research experience, knowledge, and skills. Purpose: To address these challenges, an Evidence Resource Nurse (ERN) program was developed using implementation science frameworks to enhance nurses' research literacy and skills and foster a culture of inquiry. Methods: Baseline data identified deficiencies in nurses' knowledge and confidence in utilizing research to inform practice. The ERN program was designed using the Consolidated Framework for Implementation Research and the Capability, Opportunity, Motivation, and Behavior model. The 4-hour core course is supplemented by quarterly seminars and self-paced activities in collaboration with governance councils, policy owners, and quality improvement coaches. This approach ensures that participants acquire both theoretical knowledge and practical experience in applying evidence in clinical settings. Results: The program has engaged over 100 nurses since its launch, with the latest evaluations showing improvements in participants' knowledge and skills. The program's integration into nursing professional development specialists' onboarding demonstrates institutional commitment to facilitating evidence-informed practice. Future evaluations will assess the programs' influence on nurses' initiation of evidence-informed practice changes at the unit and institutional level. Implications for Practice: The ERN program offers a model for bridging the gap between research and practice and demonstrates the use of implementation science methods to create targeted programs designed for specific populations and settings. Data-driven approaches better address nurses' professional development needs and enhance educational offerings.